Online Budget Transparency Index and its Determinants in Slovenian Municipalities - Klun, Maja; Benčina, Jože; Umek, Lan (Public Finance Quarterly, 2019)
In this article, we evaluate the online local budget transparency (OLBT) for all Slovenian municipalities and analyse the impact of various factors on the measured transparency. Most of the municipalities comply with existing regulations. The comparison of the mean values of 91 different characteristics shows that municipalities which do not comply with regulation are smaller, with poorer education structure and social position of citizens. Several municipalities are providing budget transparency beyond the legal requirements. They are smaller and less wealthy than other municipalities complying with regulation. We explain both phenomena by agency and legitimacy theory.